Management of COVID-19 related tracheal stenosis: The state of art - Orlandi, Riccardo; Raveglia, Federico; Calderoni, Matteo; Cassina, Enrico Mario; Cioffi, Ugo; Guttadauro, Angelo; Libretti, Lidia; Pirondini, Emanuele; Rimessi, Arianna; Tuoro, Antonio; Passera, Eliseo (Frontiers in Surgery, 2023)
Tracheal stenosis (TS) is a debilitating disease promoted by pathologic narrowing of the trachea. The acute respiratory distress syndrome caused by COVID-19 has been demonstrated to trigger enhanced inflammatory response and to require prolonged invasive mechanical ventilation as well as high frequency of re-intubation or emergency intubation, thus increasing the rate and complexity of TS. The standard-of-care of COVID-19-related tracheal complications has yet to be established and this is a matter of concern. This literature review aims at collecting latest evidence on this disease, providing an exhaustive overview on its distinctive features and open issues, and investigating different diagnostic and therapeutic strategies to handle COVID-19-induced TS, focusing on endoscopic versus open surgical approach. The former encompasses bronchoscopic procedures: electrocautery or laser-assisted incisions, ballooning dilation, submucosal steroid injection, endoluminal stenting. The latter consists of tracheal resection with end-to-end anastomosis. As a rule, traditionally, the endoscopic management is restricted to short, low-grade, and simple TS, whereas the open techniques are employed in long, high-grade, and complex TS. However, the critical conditions or extreme comorbidities of several COVID-19 patients, as well as the marked inflammation in tracheal mucosa, have led some authors to apply endoscopic management also in complex TS, recording acceptable results. Although severe COVID-19 seems to be an issue of the past, its long-term complications are still unknown and considering the increased rate and complexity of TS in these patients, we strongly believe that it is worth to focus on it, attempting to find the best management strategy for COVID-19-related TS.